PEMBERDAYAAN PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KULIAH KERJA NYATA DI DESA LEWOTOBI KECAMATAN ILE BURA MELALUI PROGRAM KULIAH KERJA NYATA DI DESA LEWOTOBI KECAMATAN ILE BURA - Daniel Wolo; Maria M.K. Kwuta; Helena R. Parera; Ana M. Gadi Djou (Universitas Pancasila, 2022)
Lewotobi village has great potential to improve the economy of its people. The potential consists of two, namely natural resources and human resources. Lack of knowledge and lack of motivation cause the existing potential has not been utilized optimally. Some of the problems found in the field include The absence of an internet network in the school environment and students' low awareness about the importance of education as seen from the level of participation and active participation in lessons at school. In addition, there are problems encountered in the community, such as The absence of the next generation of cultural heritage, especially from young people to become tour guides on Wato Lota beach, low awareness, and participation from residents, especially young people to take part in community service activities in the environment, there is no trench for drainage of rainwater so that most of the residents' houses are submerged in water during the rainy season. The empowerment model that is carried out for the community is a form of a participatory approach. This service activity involves the community, especially young people, to advance their village. Parents and village government assisted by facilitating capacity-building activities such as training tour guides.